Pelatihan Media Pembelajaran Komik Sains Berbasis Web Bagi Guru SMK Islamic Center Baiturrahman Semarang - Theodora Indriati Wardani; F X Didik Purwosetiyono; Rina Dwi Setyawati; Wahyuni Wahyuni (Perkumpulan Kualitama Edukatika Indonesia, 2026)
SMK Islamic Center Baiturrahman Semarang has implemented a Moodle-based Subject Information System (SIMPEL) integrated with the internet network to support the learning process. However, teachers' utilization of information and communication technology in developing digital learning media remains suboptimal. Most teachers still rely on printed textbooks and lecture-based teaching methods, resulting in monotonous learning experiences that are less engaging for students. In addition, science comics as instructional media are still produced manually, requiring considerable costs, time, and effort. To address these issues, a Community Partnership Program was conducted in the form of training on the development of web-based science comic learning media for teachers at SMK Islamic Center Baiturrahman Semarang. The training aimed to enhance teachers' competencies in developing creative, innovative, and accessible digital learning media. The activities included providing materials on the concept of digital science comics, hands-on practice in designing science comics using the Canva application, developing learning websites through Google Sites, and integrating the resulting media into the Moodle-based SIMPEL. Through this training, teachers are expected to be able to independently design and develop web-based science comics to support more engaging and interactive learning delivery. The use of digital media can also reduce dependence on printed materials, making the learning process more efficient in terms of cost, time, and effort. In addition to improving teachers' digital competencies, the developed media can be easily accessed by both teachers and students through the internet. Therefore, this program is expected to promote more effective, innovative, and technology-oriented learning practices in accordance with the demands of the digital era.